Does the perception of incongruence hurt more? Customers' responses to CSR crises affecting the main reputation dimension of a company. Issue 7 (4th May 2019) - Gistri, Giacomo; Corciolani, Matteo; Pace, Stefano
ABSTRACT: Corporate social responsibility (CSR) generates benefits for companies and society. However, CSR exposes a company to potential damage when a critical event, such as a crisis, disconfirms the CSR of a corporate reputation. The present article introduces to the crisis management literature the notion of consumer-perceived incongruence (CPI) between corporate reputation and crises. Our first experimental study demonstrates that a high CPI – compared to a low CPI – worsens consumer responses in terms of attitude towards the corporation (ATC), word of mouth (WOM) and purchase intention (PI). The second study shows that these effects are mediated by the perception of a state of discomfort on the part of the consumer. The third study suggests that, in cases of high CPI, the corporate crisis response strategy of apology outperforms that of compensation in reducing the negative effects of discomfort on consumer responses. Theoretical and managerial implications are discussed.